Femtosecond nonlinear optical properties of tellurite glasses - Souza, Rogerio F.; Alencar, Marcio A. R. C.; Hickmann, Jandir M.; Kobayashi, Renata; Kassab, Luciana R. P. (American Institute of Physics (AIP), 2006)
The third-order nonlinear optical properties of tellurite glasses with different compositions were investigated in the femtosecond regime at 810 nm. Using the I-scan technique, positive nonlinear refractive indices of similar to 10(-15) cm(2)/W were measured. The authors also determined that nonlinear absorption was negligible for all studied samples. This result, added to their good chemical stability, indicates that tellurite glasses are promising materials for ultrafast photonic applications. (c) 2006 American Institute of Physics.